Efficacy of Science Writing Heuristic Instructional Approach on Senior Secondary School Students’ Academic Achievement in Biology - Anita Ugwu, Chidinma Blessing; Aham, Assumpta Chinyere; Enebechi, Regina Ijeamasi; Nzewi, Uchenna Mariestella; Ngwu, Anthonia Ngozi; Aniaku, Obiageli Loretta; Amobi, Uchenna Vivian; Ezenwosu, Samuel Uchechukwu; Ugwu, Theresa Ukamaka; Uche, Ekwutosi Doris; Odimkpa, Christiana Ogonna (Journal of Neonatal Surgery, 2025)
This research study investigated the efficacy of science writing heuristic (SWH) approach on students’ achievement in biology. A non-equivalent control group quasi-experimental design was adopted for the study. A sample of 141 Senior Secondary year one students which comprises 57 males and 84 females drawn from four intact classes in two public co-educational secondary schools were used for the study. The experimental groups and control groups were taught using SWH approach and traditional laboratory (TL) approach respectively. Instrument used for collection of data was BAT (Biology Achievement Test) which was subjected to a reliability test using Kuder-Richardson’s formula (KR-20) and a reliability index of 0.92 was obtained. Mean and standard deviation was used to answer the research questions while ANCOVA (Analysis of Covariance) was employed to test the hypothesis at 0.05 level of significance. The findings of this study revealed that the SWH approach was more efficacious in enhancing the achievement of students in Biology than the TL approach. The findings of this study also showed that the male students achieved slightly higher than the female students when taught with the SWH approach. Moreso, there was a significant interaction effect of gender and mode of instruction on achievement of students. It was recommended that Biology teachers should employ the use of SWH approach rather than the traditional laboratory approach in carrying out practical in biology to enhance students’ achievement in Biology.